Transforming the Communications Engineering Laboratory Education through Remotely Accessible Software Radio Platform - Rong, Yue; Rajakaruna, Sumedha; Murray, Iain; Mohammadi, Nazanin; Chiong, R. (2016)
Communications engineering education has traditionally been confined to focus on theory. While it is essential that students learn the theory of communications, this alone is not enough to prepare them for their careers in telecommunications industry. This is due to the fact that there are several practical challenges in designing and implementing communication systems that are overlooked when focusing only on theory